Leptospira interrogans thermolysin refolded at high pressure and alkaline pH displays proteolytic activity against complement C3 - Rosa Maria Chura-Chambi; Tatiana Rodrigues Fraga; Ludmila Bezerra da Silva; Bruno Bernardi Yamamoto; Lourdes Isaac; Angela Silva Barbosa; Ligia Morganti (Biotechnology Reports, 2018)
Enzymes from the thermolysin family are crucial factors in the pathogenesis of several diseases caused by bacteria and are potential targets for therapeutic interventions. Thermolysin encoded by the gene LIC13322 of the causative agent of leptospirosis, Leptospira interrogans, was shown to cleave proteins from the Complement System. However, the production of this recombinant protein using traditional refolding processes with high levels of denaturing reagents for thermolysin inclusion bodies (TL-IBs) solubilization results in poor recovery and low proteolytic activity probably due to improper refolding of the protein. Based on the assumption that leptospiral proteases play a crucial role during infection, the aim of this work was to obtain a functional recombinant thermolysin for future studies on the role of these metalloproteases on leptospiral infection. The association of high hydrostatic pressure (HHP) and alkaline pH was utilized for thermolysin refolding. Incubation of a suspension of TL-IBs at HHP and a pH of 11.0 is non-denaturing but effective for thermolysin solubilization. Soluble protein does not reaggregate by dialysis to pH 8.0. A volumetric yield of 46 mg thermolysin/L of bacterial culture and a yield of near 100% in relation to the total thermolysin present in TL-IBs were obtained. SEC-purified thermolysin suffers fragmentation, likely due to autoproteolysis and presents proteolytic activity against complement C3 α-chain, possibly by a generation of a C3b-like molecule. The proteolytic activity of thermolysin against C3 was time and dose-dependent. The experience gained in this study shall help to establish efficient HHP-based processes for refolding of bioactive proteins from IBs. Keywords: Thermolysin, Metalloprotease, Refolding, High hydrostatic pressure, Alkaline pH